Existentialist Feminism of Woman’s Struggle in Cigarette Girl Novel - Faidah Yusuf; Muh. Iskandar Susilo (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
Feminism is a movement of struggle to fight against all forms of objectification of women. The main character in the Cigarette Girl novel is a very independent woman. It was analyzed through feminism approach if the literary work is related to a woman as one of the characters in the story. The objective of this research is to describe the resistances of woman’s struggle in Cigarette Girl Novel by Ratih Kumala. This reseacrh is analyzed by using descriptive qualitative method and used feminism approach to Beauvoir theory. The findings of this research are women can work, women can become intellectuals, and to transcend its boundaries. The result of this research that the women have same capability to survive in their lives as the men do therefore all the things that is point to them such as second sex, retarded, limited and weak go vague and even disappear because of the story which is told by the writer of the novel.